2014
DOI: 10.1590/s1517-83822014000400051
|View full text |Cite
|
Sign up to set email alerts
|

Nasal, oral and rectal microbiota of Black lion tamarins (Leontopithecus chrysopygus)

Abstract: Black lion tamarins (Leontopithecus chrysopygus) are endangered callithrichids. Their conservation may require future translocations or reintroductions; however these approaches involve risks of pathogen introduction in the environment and stress-related opportunistic infections in these animals. In order to screen for opportunistic and potential pathogenic bacterial and fungal microbiota, ten free-ranging and ten captive Black lion tamarins were studied and the results compared. Nasal, oral and rectal swabs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
(45 reference statements)
1
13
3
Order By: Relevance
“…In the marmosets evaluated in this study, E. coli was seldom detected in the oral cavity, and was the second most frequent species isolated from swabs of the rectum (28.6%). Similar to our findings, a study evaluating free-living and captive Leontopithecus chrysopygus (Black Lion Tamarin) showed low frequency of E.coli in the oral cavity and high frequency (the most frequent bacterium) in the rectum (Carvalho et al, 2014). Bublitz et al (2015), aiming to investigate the presence of enterobacteria in free-living NHP, evaluated samples of feces of 24 lemurs from two different areas at the perimeter of a park on the island of Madagascar: 11 animals were sampled in an area where the forest was fully preserved and 13 animals were captured in an area that had undergone strong anthropic pressure, with presence of dwellings, practice of agriculture, and raising of domestic animals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the marmosets evaluated in this study, E. coli was seldom detected in the oral cavity, and was the second most frequent species isolated from swabs of the rectum (28.6%). Similar to our findings, a study evaluating free-living and captive Leontopithecus chrysopygus (Black Lion Tamarin) showed low frequency of E.coli in the oral cavity and high frequency (the most frequent bacterium) in the rectum (Carvalho et al, 2014). Bublitz et al (2015), aiming to investigate the presence of enterobacteria in free-living NHP, evaluated samples of feces of 24 lemurs from two different areas at the perimeter of a park on the island of Madagascar: 11 animals were sampled in an area where the forest was fully preserved and 13 animals were captured in an area that had undergone strong anthropic pressure, with presence of dwellings, practice of agriculture, and raising of domestic animals.…”
Section: Discussionsupporting
confidence: 91%
“…In this kind of incident, there is also the risk of transmission of viral agents such as rabies virus and herpesvirus (Haddad Junior et al, 2013;Sobreira et al, 2019). In the present study, the bacteria isolated from the oral cavity of marmosets, are regarded as potentially pathogenic to humans, may cause severe infection, including abscess formation at the bite site (Burke et al, 2009;Carvalho et al, 2014;Sales, 2015;Singh et al, 2016;Cruz et al, 2017;Shigeno et al, 2018).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The presence of these bacteria is a consequence of the habits of Sapajus libidinosus, as they constantly put their contaminated hands, which may contain fecal material, in their mouths, and they often lick each other. E. coli are important agents of enteric diseases, specifically diarrhea, and they have been isolated from black lion tamarins (Leontopithecus chrysopygus) in captivity and are associated with morbidity and mortality 19 . In addition to the impact that E. coli can have on the health of Sapajus libidinosus, there is also the risk of transmission to humans in cases of bites.…”
Section: Discussionmentioning
confidence: 99%
“…Serratia rubidaea is detected mainly in humans with severe trauma or underlying diseases, including sepsis, bacteremia, and urinary tract infections (BONNIN et al, 2015), but it has also been found in black-lion-tamarins in Rio de Janeiro (CARVALHO et al, 2014).…”
Section: Discussionmentioning
confidence: 99%